Epigenetics and assisted reproductive technologies. (12th November 2015) - Pinborg, Anja; Loft, Anne; Romundstad, Liv B.; Wennerholm, Ulla‐Britt; Söderström‐Anttila, Viveca; Bergh, Christina; Aittomäki, Kristiina
Abstract: Epigenetic modification controls gene activity without changes in the DNA sequence. The genome undergoes several phases of epigenetic programming during gametogenesis and early embryo development, coinciding with assisted reproductive technologies (ART) treatments. Imprinting disorders have been associated with ART techniques, but disentangling the influence of the ART procedures per se from the effect of the reproductive disease of the parents is a challenge. Epidemiological human studies have shown altered birthweight profiles in ART compared with spontaneously conceived singletons. Conception with cryopreserved/thawed embryos results in a higher risk of large‐for‐gestational‐age babies, which may be due to epigenetic modification. Further animal studies have shown altered gene expression profiles in offspring conceived by ART related to altered glucose metabolism. It is controversial whether human adolescents conceived by ART have altered lipid and glucose profiles and thereby a higher long‐term risk of cardiovascular disease and diabetes. This commentary describes the basic concepts of epigenetics and gives a short overview of the existing literature on the association between imprinting disorders, epigenetic modification and ART.